2024
DOI: 10.1038/s41580-023-00682-z
|View full text |Cite|
|
Sign up to set email alerts
|

Patterning of the cell cortex by Rho GTPases

William M. Bement,
Andrew B. Goryachev,
Ann L. Miller
et al.

Abstract: The Rho GTPases-Rho, Rac and CDC42-are small GTP-binding proteins that regulate basic biological processes such as cell locomotion, cell division and morphogenesis by promoting cytoskeleton-based changes in the cell cortex. This regulation results from active (GTP-bound) Rho GTPases stimulating target proteins that in turn promote actin assembly and myosin-2-based contraction to pattern the organization of the cortex. This basic regulatory scheme, well-supported by in vitro studies, led to the natural assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 282 publications
0
7
0
Order By: Relevance
“…7e,f). The Arp2/3 complex can be activated by the CDC42/N-WASP or RAC1-WAVE2 signalling pathways to promote the cortical F-actin assembly in oocytes 9,33 . Reciprocal coimmunoprecipitation analysis further con rmed the endogenous interaction between CDC42 with N-WASP and the Arp2/3 complex, as well as the interaction between endogenous RAC1, WAVE2 and the Arp2/3 complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7e,f). The Arp2/3 complex can be activated by the CDC42/N-WASP or RAC1-WAVE2 signalling pathways to promote the cortical F-actin assembly in oocytes 9,33 . Reciprocal coimmunoprecipitation analysis further con rmed the endogenous interaction between CDC42 with N-WASP and the Arp2/3 complex, as well as the interaction between endogenous RAC1, WAVE2 and the Arp2/3 complex.…”
Section: Resultsmentioning
confidence: 99%
“…Mevalonate (MVA) pathway is crucial for cholesterol synthesis and regulates multiple cellular processes through protein prenylation, a lipidic modi cation that facilitates the anchoring of proteins to cell membranes 8 . Small GTPases could be prenylated and regulate cell division and morphogenesis by promoting cytoskeleton organization and cortex formation 9 . Recently, we reported that abnormal metabolism of the MVA pathway in granulosa cells (GCs) is an important contributing factor to meiotic defects and aneuploidy and MVA supplementation increases normal meiosis in aged oocyte 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, both in vivo Xenopus studies and in vitro analyses of mammalian epithelia show that activities of Rho GTPases and ROCKs are critical for the repair of junctional damage and for TJ remodeling to maintain barrier function ( Varadarajan et al, 2019 ). Studies in Xenopus also show a role for mechanosensitive Ca 2+ flashes and the RhoA GEF p115RhoGEF (also known as Arhgef1) in promoting RhoA activation to repair damaged TJs and thus maintaining barrier function ( Varadarajan et al, 2019 ; Bement et al, 2024 ).…”
Section: Association Of Tjs With the Actomyosin Cytoskeletonmentioning
confidence: 99%
“…Waves of F-actin and Rho activation have also been observed in the eggs and embryonic cells of frogs and starfish. In these cells, cortical waves are regulated by mitotic spindles and are implicated in cytokinesis ( Bement et al, 2024 ). Sepaniac et al studied how actin waves respond to wounding and change over the course of embryonic development in the Xenopus embryo.…”
Section: Excitability Of Cortical Actin Networkmentioning
confidence: 99%